Baccharis dracunculifolia DC (Asteraceae) selectively modulates the effector functions of human neutrophils. (10th October 2017) - Figueiredo‐Rinhel, Andréa S. G.; de Melo, Lamartine L.; Bortot, Leandro O.; Santos, Everton O. L.; Andrade, Micássio F.; Azzolini, Ana Elisa C. S.; Kabeya, Luciana M.; Caliri, Antonio; Bastos, Jairo K.; Lucisano‐Valim, Yara Maria
Abstract: Objectives: To examine whether the hydroalcoholic extract from Baccharis dracunculifolia leaves (BdE) modulates the human neutrophil oxidative metabolism, degranulation, phagocytosis and microbial killing capacity. Methods: In‐vitro assays based on chemiluminescence, spectrophotometry, flow cytometry and polarimetry were used, as well as docking calculations. Key findings: At concentrations that effectively suppressed the neutrophil oxidative metabolism elicited by soluble and particulate stimuli (<10 μg/ml), without clear signs of cytotoxicity, BdE (1) inhibited NADPH oxidase and myeloperoxidase activity; (2) scavenged H2 O2 and HOCl; (3) weakly inhibited phagocytosis; and (4) did not affect neutrophil degranulation and microbial killing capacity, the expression levels of TLR2, TLR4, FcγRIIa, FcγRIIIb and CR3 and the activity of elastase and lysozyme. Caffeic acid, one of the major B. dracunculifolia secondary metabolites, did not inhibit phagocytosis but interfered in the myeloperoxidase–H2 O2 –HOCl system by scavenging H2 O2 and HOCl, and interacting with the catalytic residues His‐95, Arg‐239 and Gln‐91. Conclusions: BdE selectively modulates the effector functions of human neutrophils, inhibits the activity of key enzymes and scavenges physiological oxidant species. Caffeic acid contributes to lower the levels of oxidant species. Our findings help to unravel the mechanisms by which these natural products exert immunomodulatory action towards neutrophils.